INOVASI ALAT PENCACAH GELAS PLASTIK DAN DAUN KERING DI DESA PADANGBANDUNG GRESIK (Lembaga Penelitian Dan Pengabdian Kepada Masyarakat Universitas 17 Agustus 1945 Surabaya, 2019)
Garbage is a problem in most parts of Indonesia, one of them in Padangbandung Village, Dukun, Gresik. Crunching with these problems came the idea to create a chopper machine that was more specifically for plastic cups and leaves. With the aim of plastic glass trash can be reused or recycled while the results of enumeration of leaves can be used for making compost. This work program can be run if all parties can work together from the community to the village government. First, the village government must facilitate the trash that distinguishes between organic and inorganic waste, so that people can dispose of waste according to its type to facilitate the enumeration process. To overcome the problem of waste, we must make a reduction in terms of use while providing innovation so that the waste we produce can be recycled or reused, one of which is the inno vation of plastic glass chopper whose output can be used instead of fiber, as a protective packaging furniture glassware, and can also be sold as plastic recycling materials.